Investigation of Vertical Deformation around Trabzon Tide Gauge Station - YILMAZ, Nazan; DEMIRSOY, Nilüfer (GeoScience Engineering, 2021)
Nowadays, with the rapid development of technology, the importance of deformation measurement is increasing. Measuring the shape and position changes of natural or artificial structures as a result of external factors are called deformation measurements. In order to determine deformations, geodetic control networks are generally established and measurements are made at various periods in these networks. Deformation analysis is performed using the point coordinates obtained by evaluating the measurements made. GPS is generally used for horizontal and vertical directions and precision levelling method is generally used for vertical direction only in determining deformation in geodetic control networks. Measurements made in different periods are tested with deformation models and it is investigated whether there is deformation in the passing time. In this study, we aimed to examine the vertical crust movements in and around the tide gauge station in Trabzon harbour area. For this purpose, in a leveling network established in the study area, precision levelling measurements were made in two periods, June 2020 (1st period) and October 2020 (2nd period). The measured height differences were adjusted according to the free network method. In both periods, the t-distributed inconsistent test was applied and an inconsistent measure was found for a single route. Adjustment was made by removing the inconsistent measurements found. We investigated whether there has been any movement in the network between two periods by using the θ2-criterion method, one of the static deformation model methods. The vertical movements that may occur between different periods have been determined and we investigated whether there is a vertical deformation around the tide gauge station. The calculations regarding the methods applied within the scope of the study were made using MATLAB program codes written by us. Keywords: Adjustment; Deformation; Precise Levelling; Tide gauge; θ2-Criteria Method